Intermittent versus continuous drought: chlorophyll a fluorescence reveals photosystem resilience in tomato - Peco, Jesús D.; Centeno, Ana; Moratiel, Rubén; Villena, Jaime; López-Perales, Jesús A.; Moreno, Marta M.; Pérez–López, David (Frontiers in Plant Science, 2025)
IntroductionRecurrent drought threatens Mediterranean tomato yields, yet how the time-scale of drought shapes photochemical tolerance remains unclear.MethodsWe evaluated six genotypes, three commercial cultivars (‘Sintonía’, ‘Marejada’, ‘Valenciano’) and three Mediterranean landraces (‘82’, ‘264’, ‘260’, under greenhouse conditions. Plants received either two short pulses (WS1) or a single prolonged drought (WS2). We tracked stem water potential (Ψstem) and computed a stress integral (SI), and measured gas exchange, leaf chlorophyll, and chlorophyll a fluorescence (OJIP test) across key time points and after rewatering.ResultsThe first WS1 pulse transiently increased performance index (PIABS) and electron‑transport efficiencies (ΨE0, ϕE0) by 20–40 % in four cultivars. Photosynthesis declined by –70 to –80 % but recovered within three days of irrigation. ‘Sintonía’ showed early increases in dissipation (ϕD0) and fluxes (ABS/CS0, DI0/CS0), while maximum quantum yield (ϕP0) remained unchanged across genotype. Sustained WS2, however, reduced PIABS and ϕP0 by –18 to –50 %, increased ϕD0, ABS/CS0 and DI0/CS0 by 30–60 % in all except ‘260’, whose OJIP profile remained stable. Photosynthesis dropped near zero but recovered in five genotypes; ‘264’ recovered only 50 %, showing irreversible damage. Chlorophyll content stayed constant, so shifts were pigment‑independent.DiscussionFindings support a three-stage resilience model: (i) reversible photoprotective adjustment to short severe drought; (ii) cumulative photochemical damage under sustained deficit; and (iii) genotype-dependent recovery.ConclusionCombining temporal stress integrals with OJIP screening provides a robust pipeline for breeding Mediterranean tomatoes adapted to future drought, advancing knowledge of drought resilience mechanisms.